Manejo de Antracnosis (Colletotrichum sp.) en el cultivo de guanábana (Annona muricata L.) - Bonilla Contreras, Vicente Josue (2022)
This document compiled relevant information on the management of Anthracnose (Colletotrichum sp.) in the cultivation of soursop (Annona muricata L.). Anthracnose causes black rot of fruit and affects all stages of fruit development, mainly in the soft tissues. The fruit mummifies and falls off; in nursery plantations it occurs causing necrosis of the branch neck and the branch tip. In addition, it was determined that the fungus Colletotrichum sp. it attacks plantations from the nursery stage to the final site or plants in production, affecting leaves, flowers, shoots, branches and fruits, with lesions that start small and are dark brown in color and increase to a black hue; environmental conditions, such as high rainfall, promote the development of the pathogen; the branches attacked by Colletotrichum are the cause of the black rot of the fruit and the control can be carried out by eliminating or burning infected fruits and plants and also by pruning, together applying fungicides based on copper hydroxide, mancozeb or chlorothalonil